Application of The Execution of Fiduciary Guarantees on Movable Objects to Defendant Creditors: (Analysis of Decision Number 70/Pdt.GS/2020/Pn Palembang) - Diana Setiawati; Enora Aulia Purbayang (Universitas Muhammadiyah Surakarta, 2023)
In the difficult economic situation due to the Covid-19 outbreak, many people carry out credit transactions to meet their daily needs. In these credit transactions, many debtors are late in paying installments due to declining economic factors. The execution process often becomes a dispute, because the creditor has defaulted by not fulfilling his obligations and executing the fiduciary guarantee without showing the documents related to the guarantee. The research method applied is normative juridical, this type of research is descriptive qualitative which aims to describe and analyze various formal regulations in the context of fiduciary guarantees. The data source applied is data originating from the results of literature research relating to fiduciary guarantees. The data collection technique applied is a normative research method, namely by collecting various types of legal materials ranging from primary legal materials, secondary legal materials, to tertiary legal materials. The data analysis method applied is a qualitative method and is presented descriptively. The results of the research are contained in the conclusion which shows that Decision number 70/Pdt.GS/2020/PN.Plg which granted part of the plaintiff's demands shows that in the execution of fiduciary guarantees on movable objects against defaulting creditors, there are various types of violations committed by creditors against statutory regulations - valid invitation.The debtor's legal protection in this case is still relatively weak and detrimental to the plaintiff, because the sanctions imposed on creditors are still limited to administrative sanctions. Meanwhile, protection for creditors in this case is still relatively weak, because creditors only receive repressive legal protection.